Chemically activatable viral capsid functionalized for cancer targeting. (February 2016) - Chen, Chun-Chieh; Xing, Li; Stark, Marie; Ou, Tingwei; Holla, Prasida; Xiao, Kai; Kamita, Shizuo G; Hammock, Bruce D; Lam, Kit; Cheng, R Holland
Aim: To design a theranostic capsule using the virus-like nanoparticle of the hepatitis E virus modified to display breast cancer cell targeting functional group (LXY30).Methods: Five surface-exposed residues were mutated to cysteine to allow conjugation to maleimide-linked chemical groups via thiol-selective linkages. Engineered virus-like nanoparticles were then covalently conjugated to a breast cancer recognized ligand, LXY30 and an amine-coupled near-infrared fluorescence dye.Results: LXY30-HEV VLP was checked for its binding and entry to a breast cancer cell line and for tumor targeting in vivo to breast cancer tissue in mice. The engineered virus-like nanoparticle not only targeted cancer cells, but also appeared immune silent to native hepatitis E virus antibodies due to epitope disruption at the antibody-binding site.Conclusion: These results demonstrate the production of a theranostic capsule suitable for cancer diagnostics and therapeutics based on surface modification of a highly stable virus-like nanoparticle.